EVALUATING AND OPTIMIZING THE HAULED CONTAINER SYSTEM (HCS) IN PT. KAMIBOX MAJU SEJAHTERA'S WASTE MANAGEMENT OPERATION - Mubaroq, Ahmad Zakhi; Sari, Mega Mutiara; Suryawan, I Wayan Koko (Fakultas Teknik Universitas Tanjungpura, 2024)
This study evaluates the Hauled Container System (HCS) used in PT. Kamibox Maju Sejahtera's waste management operations. The HCS is a transportation method to transport containers filled with waste and recyclables from collection points to processing or disposal facilities, at PT. Kamibox Maju Sejahtera vehicles travel from a centralized hub in Cisauk to specific pickup locations to load containers. Each vehicle typically handles one location per operational cycle and then transports the loaded container to its destination. Our analysis shows that the HCS system currently enables approximately 2.45 trips per day, which translates to two practical daily trips. This system's simplicity and directness provide ease of management and reduce contamination risk, reassuring the audience about its current effectiveness. The study further explores fuel efficiency and costs, revealing that while the Gran Max is the most fuel-efficient, the Colt Diesel is the most cost-effective. Recommendations include optimizing vehicle use and considering more fuel-efficient alternatives to improve sustainability and reduce operational costs. The findings serve as a guide for PT. Kamibox Maju Sejahtera and similar enterprises were aiming for sustainable waste management.